2001
DOI: 10.1190/1.1487120
|View full text |Cite
|
Sign up to set email alerts
|

Application of Alford rotation to ground-penetrating radar data

Abstract: We investigate the application of Alford rotation to ground‐penetrating radar (GPR) data. By recording the reflected field amplitudes using four different configurations, we extract information about the orientation of buried objects that have angle‐dependent reflectivity. In theory this method can be successfully applied to find the orientation of dipping layers, cylinders, and vertical fractures. Modeling results show angle‐dependent reflections in all three cases; as a result, we can exactly determine the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…In this way we can estimate the instantaneous amplitudes as if the antennas have recorded the scattered field with the new orientation. This Alford rotation can produce new images of the two co‐polar or cross–dipole configurations at any angle of orientation (Van Gestel and Stoffa ).…”
Section: Methodsmentioning
confidence: 99%
“…In this way we can estimate the instantaneous amplitudes as if the antennas have recorded the scattered field with the new orientation. This Alford rotation can produce new images of the two co‐polar or cross–dipole configurations at any angle of orientation (Van Gestel and Stoffa ).…”
Section: Methodsmentioning
confidence: 99%
“…Over the past few years, many theoretical and experimental studies have been carried out to underline the advantages of acquiring multi‐component GPR data (Van Gestel and Stoffa , , ; Radzevicius and Daniels ; Radzevicius et al ).…”
Section: State Of the Artmentioning
confidence: 99%
“…Some authors (Van Gestel and Stoffa , ; Radzevicius and Daniels ; Radzevicius et al ) proposed using the Alford rotation operator to determine the orientation angle of targets which are characterized by directionality. The same method was also used to improve some migration algorithms (Van Gestel and Stoffa ).…”
Section: State Of the Artmentioning
confidence: 99%
“…3,4 This approach produced good results when extracting linearity and orientation features from the late-time response of subsurface unexploded ordnance (UXO) 3 and determining the orientation of geological structures and pipes 4 . In this paper, a frequency domain approach was chosen since experience showed that diagonalization results are easier to interpret when working with scattering matrices that are scaled by the incident field through multiplication rather than convolution.…”
Section: Introductionmentioning
confidence: 97%